2020
DOI: 10.1111/pde.14503
|View full text |Cite
|
Sign up to set email alerts
|

Light‐based treatment of pediatric port‐wine birthmarks

Abstract: Port-wine birthmarks (PWBs), often referred to as port-wine stains or capillary malformations, are progressive malformations composed of capillaries and post-capillary venules. They occur in up to 0.3% of newborns, present at birth as a pink to red patch, and often involve cosmetically sensitive areas including the face. 1 Over time, many PWBs darken in color, acquire secondary changes, including nodules and pyogenic granulomas, and develop soft-tissue hypertrophy that may involve underlying structures. 2,3 PW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
5
0
1
Order By: Relevance
“…Laser-associated purpura is a common complication. 12 This was also observed in our study. It is the most favorable endpoint for PDL, which was used in the majority of our patients.…”
Section: F I G U R Esupporting
confidence: 90%
See 2 more Smart Citations
“…Laser-associated purpura is a common complication. 12 This was also observed in our study. It is the most favorable endpoint for PDL, which was used in the majority of our patients.…”
Section: F I G U R Esupporting
confidence: 90%
“…Other light‐based therapeutic options, such as long‐pulse alexandrite or long‐pulse Nd:YAG, which provide greater penetration depth, may have a role in treating these lesions. However, these lasers carry a higher risk of causing scars and pigmentation, which can lead to unfavorable outcomes 12,13 . In terms of distribution, many studies have reported that the centrofacial area and S2 are associated with poor outcomes 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interval between treatments varies within the literature, with most studies reporting intervals from 2 to 6 weeks. There does not seem to be a considerable improvement in clearance rates with more frequent treatments, but populations of skin of color may demonstrate greater adverse effects with treatment intervals of 2 weeks [4].…”
Section: Port-wine Birthmarks and Capillary Malformationsmentioning
confidence: 95%
“…Intense pulsed light (IPL) therapy has been studied in adults to improve meibomian gland (MG) secretion, reduce eyelid telangiectasias, and eradicate blepharitic Demodex mainly through the photothermal effect [ 11 ]. From toddlers to adolescents, IPL has been frequently employed in the dermatology field concerning the removal of facial hair and port-wine birthmark, the impediment of scar formation, with no remarkable side effects documented [ 12 , 13 , 14 , 15 ]. However, few published articles have discussed the feasibility of IPL in pediatric blepharitis.…”
Section: Introductionmentioning
confidence: 99%